A STUDY ON THE INFLUENCE OF RETAIL VISUAL MERCHANDISING ON IMPULSE PURCHASES AND CUSTOMER LOYALTY INTENTIONS IN TRICHIRAPPALLI CITY: A PRACTICAL STUDY WITH SPECIAL REFERENCE TO BRANDED READY-MADE MEN'S APPAREL. (International Journal of Food and Nutritional Sciences, 2022)
The term "retail" originates from the French word "retailer," signifying "to break the mass." Consequently, a retailer can be described as a vendor or merchant who sells small quantities of items to a broad customer base.Information was gathered from 193 participants through the application of Simple Random Sampling. The chosen research methodology is descriptive research. The sample size was determined using a 95 percent confidence level, a 5% margin of error, and a 50 percent population proportion, resulting in a final sample size of 385. I utilized half of this final count. A total of 193 respondents actively participated in the study. A preliminary questionnaire test involved a sample size of 15 individuals, primarily conducted to verify the authenticity of the instrument.